Heritage in Action : Making the Past in the Present - Silverman, Helaine; Waterton, Emma; Watson, Steve (Springer International Publishing : Imprint: Springer, 2017)
In this textbook we see heritage in action in indigenous and vernacular communities, in urban development and regeneration schemes, in expressions of community, in acts of nostalgia and memorialization and counteracts of forgetting, in museums and other spaces of representation, in tourism, in the offices of those making public policy, and in the politics of identity and claims toward cultural property. Whether renowned or local, tangible or intangible, the entire heritage enterprise, at whatever scale, is by now inextricably embedded in "value". The global context requires a sanguine approach to heritage in which the so-called critical stance is not just theorized in a rarefied sphere of scholarly lexical gymnastics, but practically engaged and seen to be doing things in the world.
Keywords: Social sciences.; Cultural heritage.; Archaeology.; elektronické knihy; electronic books